Techno-economic multi-objective optimization of detailed external wall insulation scenarios for buildings in moderate-dry regions. (August 2021) - Motaghian, Shahrooz; Monajati Saharkhiz, Mohammad Hossein; Rayegan, Saeed; Pasdarshahri, Hadi; Ahmadi, Pouria; Rosen, Marc A.
Highlights: The optimum insulation scenarios (thickness and placement) are presented. Economic investigations are conducted for local and international prices. Insulation layers are taken to vary continuously to cover infinite arrangements. Optimum points are obtained for various external wall configurations. The results apply and are practical for moderate and dry climates. Abstract: In this paper, the advantages of using insulation on building external walls are investigated via a dynamic simulation–optimization technique. The insulation layers are assumed to vary continuously in the external walls in order to cover infinite placement scenarios, for moderate and dry regions. First, the best insulation placement and thickness is proposed based on the total cost of a typical building by a single-objective optimization. Then, multi-objective optimization is conducted considering both energy and environmental and economic indicators to find the best insulation scenarios. Both subsidized and international prices are addressed in the economic assessment. Total insulation thicknesses of 3.20 cm and 7.00 cm are suggested for subsidized and international prices, respectively, based on single-objective optimization. With the results, the overall thickness and placement of insulation layers significantly affect utility savings, and a set of optimum points exhibiting the best insulating arrangements can be determined. Moreover, when energy resources are supplied at subsidized prices, constructors tend to retrofit buildings with thinner layers, lowering opportunities of reducing energy demands by modifying building insulation.